Pengukuran Iklim Keselamatan Dan Perilaku Keselamatan Di Perusahaan Jasa Bongkar Muat - Estianda Putri Meita Sari; Lukman Handoko; Ponti Almas Karamina (Journal of Safety, Health, and Environmental Engineering, 2024)
Occupational safety is one of the main factors that must be considered by companies when maintaining the welfare of the workforce. Safety climate refers to the degree of collaboration between individuals and organizations, reflecting the temporary state of affairs in safety culture. Safety behavior involves the planned application of psychological principles regarding human behavior to safety issues in the work environment. The purpose of this study is to measure the extent to which safety climate and safety behavior are implemented in the company environment. This research method involves the use of a questionnaire given to lift and transport operators in companies engaged in loading and unloading services. This questionnaire is based on the Nordic Safety Climate Questionnaire and consists of seven dimensions with a total of 50 questions. Safety Observation Checklist is an observation method used in the industrial sector. This method is used to observe worker safety behavior in several main aspects and several other instruments. All observation items are translated into 7 statement items contained in an observation sheet called the Safety Observation Checklist. Based on the results of the safety climate analysis for lift operators in loading and unloading service companies, there is a low value when compared to the values in other dimensions. There are three dimensions that have the lowest score where the score is less than 2.70. As for the assessment of safety behavior using the observation method that has been carried out, there is a value that is said to be low.